Overexpression of Copper/Zinc Superoxide Dismutase in the Organum Vasculosum of the Lamina Terminalis (OVLT) Attenuates Chronic Angiotensin II-Induced Hypertension in the Rat - Collister, John P.; Taylor-Smith, Heather; Drebes, Donna; Nahey, David; Tian, Jun; Zimmerman, Matthew C. (New Horizons in Medicine and Medical Research Vol. 9, 2022)
To modulate blood pressure, angiotensin II (AngII) can enter the brain via circumventricular organs (CVOs), such as the subfornical organ (SFO) and the organum vasculosum of the lamina terminalis (OVLT). We investigated whether higher levels of superoxide \(\left(O_{2}^{-}\right)\) in the OVLT have a role in the hypertensive effects of AngII. Adenoviral vectors encoding human copper/zinc superoxide dismutase (CuZnSOD) or control adenovirus (AdEmpty) were injected directly into the OVLT of rats to enable superoxide dismutase overexpression. After three days of saline infusion, rats were given AngII (10 ng/kg/min) intravenously for ten days. Blood pressure increased 33 ± 8 mmHg in AdEmpty rats rats (n = 6), while rats overexpressing CuZnSOD (n = 8) in the OVLT demonstrated a blood pressure increase of only 18 ± 5 mmHg after 10 days of AngII infusion. These findings support the theory that excessive \(\left(O_{2}^{-}\right)\) generation in the OVLT contributes to the development of chronic AngII-dependent hypertension.